Screening of Plant Growth-Promoting Halotolerant Bacteria Isolated from Weeds Rhizosphere Grown in Saline Soil - Luqman Qurata Aini; Nurul Aini; Wiwin Sumiya Dwi Yamika; Adi Setiawan (AGRIVITA, Journal of Agricultural Science, 2022)
This study aimed to screen and characterize halotolerant bacterial isolates, which could enhance plant growth performance in saline soil. Halotolerant bacteria was isolated from weeds rhizosphere grown in saline soil of coastal agricultural land located at Brondong District, Lamongan Regency, East Java Province, Indonesia. This research was conducted from June to September 2018. Seven bacterial isolates can grow in a Nutrient Agar medium containing 10% of NaCl, suggesting that these bacteria were halotolerant. Furthermore, all bacterial isolates were shown to produce indol acetic acid (IAA) and do not induce a hypersensitive response when infiltrated into tobacco leaves. These results explain that these bacteria had potency as plant growth-promoting rhizobacteria (PGPR) and were not tend to be the plant pathogen. The growth of seedlings when inoculated in cucumber seed grown in saline media were higher than those in control. This result suggests that the halotolerant bacteria can enhance the development of cucumber seedlings in saline stress conditions. Three potential halotolerant bacteria i.e., SN22, SN23, SN26 were selected and molecularly identified as Bacillus megaterium, Bacillus sp., and B. megaterium, respectively.